Comparing the fetal and maternal outcomes of dual endocrinopathy with that of isolated gestational diabetes mellitus and hypothyroidism in Indian pregnant women - Pothanis, Pranav; Jois, Srinivas K.; Jayarajan, Vishnu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Both diabetes mellitus and hypothyroidism are known to cause adverse effects for mother and fetus, however, their combined effect has not been adequately studied in the Indian context. This study aimed to fill that gap. Methods: A prospective cohort study was conducted with three groups. Group 1 consisted of mothers diagnosed with gestational diabetes mellitus only (n=61), group 2 consisted of hypothyroidism only (n=55) and group 3 consisted of pregnant patients diagnosed with both gestational diabetes mellitus and hypothyroidism (n=35). These three groups were followed up from the time of diagnosis, for up to one week following delivery. The maternal outcomes assessed include premature rupture of membranes, preterm labour and preeclampsia. Fetal outcomes include APGAR scores at 1 minute and 5 minutes, NICU admission and birth weight. Results: Amongst the three groups, mothers with gestational diabetes mellitus had the highest birth weights of babies (2.99±0.61 kg), followed by dual endocrinopathy group (2.44±0.76 kg) , and lastly, by hypothyroidism group (2.22±0.71 kg). Other outcomes did not have any significant association with type of endocrinopathy. Conclusions: Pregnant patients diagnosed with hypothyroidism alone have chances of having babies who are small for gestational age whereas the other two groups are likely to have large for gestational age babies. Further studies are required to confirm this finding.